Bodies in Dependence: A Foucauldian Genealogy of the Americans with Disabilities Acts - Skyer, Michael E. (Disability Studies Quarterly, 2019)
The Americans with Disabilities Acts (ADA) of 1990 and 2008 are laws imagined as enacting two goals: enhancing civil rights and reducing sociopolitical discrimination for Americans with disabilities; however, findings from this study strongly contrast with popular assumptions about the ADA. Key findings show how the ADA legitimizes governmental control of disability through discourse to consolidate economic power. The study employs the genealogical method, derived from Foucault, which is used to identify destructive and productive operations of power and identify ambiguities in discursive regimes. The ADA constructs a discursive category of "disability," the results of which are contradictory and problematic, evincing an asymmetrical power distribution between governmentality and people with disabilities. In the ADA, disabled people are conflated with abnormal bodies. The ADA's rhetorical construction of disability suggests that constructing a unified "disabled body" allows for individuals with disabilities to be defined and then controlled en masse. Events and rhetoric surrounding the ADA's passage illuminate how it regulates disabled individuals, described as untapped sources of economic potential. This genealogy uncovers findings indicating disturbing facts. For instance, the ADA articulates disabled bodies in service of capitalistic exploitation rather than human liberation. Similarly, the ADA generates a unique form of discursive hegemony that aims to control the bodies, minds, and perhaps the souls of Americans with disabilities.